Pigments from Microorganisms: A Sustainable Alternative for Synthetic Food Coloring - Akshay Chavan; Jaya Pawar; Umesh Kakde; Mekala Venkatachalam; Mireille Fouillaud; Laurent Dufossé; Sunil Kumar Deshmukh (Fermentation, 2025)
Microbial pigments are gaining acceptance as a green, sustainable substitute for synthetic food pigments due to growing health issues and their adverse health impacts. This review provides an overview of the potential of microbial pigments as natural food colorants and the advantages of microbial pigments over synthetic pigments. Microbial pigments are a natural source of color with medicinal properties like anticancer, antimicrobial, and antioxidant activity. Important pigments covered are astaxanthin, phycocyanin, prodigiosin, riboflavin, β-carotene, violacein, melanin, and lycopene, and their microbial origins and characteristics. The review also covers commercial production of microbial pigments, i.e., strain development and fermentation processes. Microbial pigments also find extensive applications in food industries, including preservatives for food. Also covered are their pharmacological activity and other applications, such as in the formation of nanoparticles. Finally, the challenges and future directions of microbial pigment production are covered, including the need for cost-effective production, regulatory acceptability, and the potential of genetic engineering and fermentation-based technologies to enhance pigment yield and quality.